Hubungan Komitmen Organisasi dan Kepuasan Kerja Karyawan di Universitas Proklamasi 45 Yogyakarta - Wartono Wartono; Dewi Handayani Harahap (Jurnal Psikologi, 2023)
This research wash airned to know the correlation between organizational commitmen and job satisfaction. Research subject is employee whose worked as employee of Universitas Proklamasi 45 Yogyakarta some 50 people. Method of research is quantitative with population reseach. Data collection tool using Organizational Commitment Scale and Job Satisfaction Scale. Methods of data analysis in this study using a product moment correlation analysis techniques. The results showed a correlation value of rxy = 0,358 with a significance level of p = 0,000 (p <0.01). Value of R² = 0,128. This means that the effective amount of donations given organizational commitment in increasing job satisfaction variables of 12,8%. Most of the subject as many as 42% had job satisfaction in the middle category and 54% have organizational commitment in the high category. The results show that there is a very significant positive correlation between organizational commitmen and job satisfaction. The more higher organizational commitment, the higher employee job satisfaction, where as the more lower organizational commitment, the lower employee job satisfaction.